Total synthesis of the reported structure of bioactive dibenzofuran natural product karnatakafuran B. (6th April 2023) - Hieda, Yuhzo; Une, Yohsuke; Satoh, Akihiro; Tsuruga, Takayoshi; Choshi, Tominari
Abstract: In this study, the first total synthesis of the reported structure of karnatakafuran B was accomplished through an 11-step reaction sequence using an allene-mediated electrocyclization of a 6π electron system involving a benzofuran [ b ]-bond for the construction of a highly substituted dibenzofuran ring. The spectral data of the synthesized compound was not identical to that of the natural karnatakafuran B. Graphical abstract: To create your abstract, type over the instructions in the template box below.Fonts or abstract dimensions should not be changed or altered. Image 1 Highlights: The first total synthesis of the reported structure of karnatakafuran B was accomplished through an 11-step reaction sequence. 2, 3, 4, 6-tetrasubstituted benzofuran was synthesized from 2-methoxyacetophenone derivative by the gram-scalable route. The dibenzofuran framework was constructed by the allene-mediated electrocyclization of a 6π hexatriene system.